2018
DOI: 10.3389/fphys.2018.00572
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Terrestrial Environments: Life in Thermal Stress and Hypoxia. A Narrative Review

Abstract: Living, working and exercising in extreme terrestrial environments are challenging tasks even for healthy humans of the modern new age. The issue is not just survival in remote environments but rather the achievement of optimal performance in everyday life, occupation, and sports. Various adaptive biological processes can take place to cope with the specific stressors of extreme terrestrial environments like cold, heat, and hypoxia (high altitude). This review provides an overview of the physiological and morp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 170 publications
(234 reference statements)
0
51
0
3
Order By: Relevance
“…Abrupt exposure to higher altitudes (>3,500 m above sea level) can cause acute mountain sickness and can lead to complications, including HACE, high-altitude pulmonary oedema, reduced body heat metabolism in plateau, increased evaporation, and significant dehydration, which in turn lead to increased difficulty in treatment of TBI (24,25). To the best of our knowledge, no previous reports have described the neurological, pathophysiology and imaging characteristics of the acute phase of mmCHI at varying high-altitudes.…”
Section: Discussionmentioning
confidence: 99%
“…Abrupt exposure to higher altitudes (>3,500 m above sea level) can cause acute mountain sickness and can lead to complications, including HACE, high-altitude pulmonary oedema, reduced body heat metabolism in plateau, increased evaporation, and significant dehydration, which in turn lead to increased difficulty in treatment of TBI (24,25). To the best of our knowledge, no previous reports have described the neurological, pathophysiology and imaging characteristics of the acute phase of mmCHI at varying high-altitudes.…”
Section: Discussionmentioning
confidence: 99%
“…Acute cold exposure results in a series of behavioral and homoeostatic responses to reduce heat flow from the core to the environment and maintain core body temperature . Cutaneous vasoconstriction and thermogenesis are the most important mechanisms.…”
Section: Physiological Response and Rate Of Cooling During Acute Coldmentioning
confidence: 99%
“…Acute cold exposure results in a series of behavioral and homoeostatic responses to reduce heat flow from the core to the environment and maintain core body temperature. 22,23 Cutaneous vasoconstriction and thermogenesis are the most important mechanisms. Peripheral vasoconstriction reduces peripheral blood flow and thus minimizes convective heat flow to the environment when a temperature gradient exists between skin and ambient temperature.…”
Section: And Rate Of Cooling During Acute Cold Exposurementioning
confidence: 99%
“…It is well known that hypoxia resulted from chronic high altitude produces an increase in hemoglobin concentration as well as red blood cell count and hematocrit values. [1][2] In addition, recently Akunov et al (2018) concluded that hemoglobin levels have a linear relationship with the duration of exposure to intermittent hypoxia. 3 This increase in the levels of hemoglobin or hematocrite levels result in an increase in x-ray attenuation within the vasculature ,4 which may lead to variability between patients in the radiodensity on CT images within the intracranial vasculature.…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%